A visual cortical-lateral posterior thalamic nucleus circuit regulates depressive-like behaviors in male mice - Fangfang Wu; Chenxi Gu; Rui Xu; Junwei Ma; Lei Gao; Youjiao Zhang; Siyuan Bu; Qingbo Lu; Te Zhao; Yijun Han; Chen Guo; Yihui Cui; et al. (Nature Communications)
Abstract Depression, a prevalent psychiatric disorder of ambiguous etiology and high heterogeneity, has been recently linked to the primary visual cortex (V1). However, the precise circuits mediating the impact of V1 on depressive-like behaviors are poorly understood. Here, we demonstrate that the V1, specifically the lateral posterior nucleus of the thalamus (LP)-projecting V1 glutamatergic subpopulation (GluV1→LP neurons), shows reduced activity after chronic restraint stress (CRS) in male mice, leading to depressive-like behaviors. Optogenetic or chemogenetic activation of these neurons ameliorated depressive-like behaviors in CRS-depressed mice, whereas reducing activity exacerbated these behaviors. This reduction in GluV1→LP neurons activity was predominantly due to a decrease in the guanine nucleotide-binding protein subunit gamma-4 (Gγ4). Overexpression of Gγ4 in the GluV1→LP neurons produced antidepressant-like effects, suggesting that Gγ4 is a crucial regulator of mood. Collectively, these results reveal a V1→LP circuit that modulates depressive-like behaviors, suggesting potential targets for therapeutic interventions.